Repeated and Interrupted Resistance Exercise Induces the Desensitization and Re-Sensitization of mTOR-Related Signaling in Human Skeletal Muscle Fibers - Jacko, Daniel; Schaaf, Kirill; Masur, Lukas; Windoffer, Hannes; Aussieker, Thorben; Schiffer, Thorsten; Zacher, Jonas; Bloch, Wilhelm; Gehlert, Sebastian (International journal of molecular sciences, 2022)
The acute resistance exercise (RE)-induced phosphorylation of mTOR-related signaling proteins in skeletal muscle can be blunted after repeated RE. The time frame in which the phosphorylation (p) of mTORS2448, p70S6kT421/S424, and rpS6S235/236 will be reduced during an RE training period in humans and whether progressive (PR) loading can counteract such a decline has not been described. (1) To enclose the time frame in which pmTORS2448, prpS6S235/236, and pp70S6kT421/S424 are acutely reduced after RE occurs during repeated RE. (2) To test whether PR will prevent that reduction compared to constant loading (CO) and (3) whether 10 days without RE may re-increase blunted signaling. Fourteen healthy males (24 ± 2.8 yrs.; 1.83 ± 0.1 cm; 79.3 ± 8.5 kg) were subjected to RE with either PR (n = 8) or CO (n = 6) loading. Subjects performed RE thrice per week, conducting three sets with 10–12 repetitions on a leg press and leg extension machine. Muscle biopsies were collected at rest (T0), 45 min after the first (T1), seventh (T7), 13th (T13), and 14th (X-T14) RE session. No differences were found between PR and CO for any parameter. Thus, the groups were combined, and the results show the merged values. prpS6S235/236 and pp70s6kT421/S424 were increased at T1, but were already reduced at T7 and up to T13 compared to T1. Ten days without RE re-increased prpS6S235/236 and pp70S6kT421/S424 at X-T14 to a level comparable to that of T1. pmTORS2448 was increased from T1 to X-T14 and did not decline over the training period. Single-fiber immunohistochemistry revealed a reduction in prpS6S235/236 in type I fibers from T1 to T13 and a re-increase at X-T14, which was more augmented in type II fibers at T13 (p < 0.05). The entity of myofibers revealed a high heterogeneity in the level of prpS6S235/236, possibly reflecting individual contraction-induced stress during RE. The type I and II myofiber diameter increased from T0 and T1 to T13 and X-T14 (p < 0.05) prpS6S235/236 and pp70s6kT421/S424 reflect RE-induced states of desensitization and re-sensitization in dependency on frequent loading by RE, but also by its cessation.